Screening and Integration Analysis of OsDREB1A BC4F2 and BC5F1 Generations of Transgenic Ciherang Rice (Oryza sativa L.) for High-Salinity Tolerance - Priyono, Dika Migi; Santoso, Tri Joko; Salamah, Andi (Makara Journal of Science, 2013)
Salinity is one of a number of abiotic stresses that threaten rice production in Indonesia. To support food security programs, BB-Biogen has developed rice lines derived from OsDREB1A transformed Ciherang up to BC4F2 and BC5F1 generations. To verify the salinity tolerance and the stability of transgene integration, the BC4F2 and BC5F1 generations of Ciherang-OsDREB1A transgenic were screened to select high-salinity tolerant lines. Second, molecular analysis using the primers hptII-F/hptII-R and 35S-496-F/OsDREB1A-R was conducted to identify the existence and the stability of the transgene integration in the BC4F2 and BC5F1 generations. Screening 543 BC4F2 and BC5F1 Ciherang-OsDREB1A transgenic lines in a nutrient solution with a final electrical conductivity (EC) of approximately 18 mS/cm for 26 days yielded 134 putative transgenic plants. Integration analysis using the hptII-F/hptII-R primers showed that 73 of the 134 putative transgenic plants had positive PCR products, indicating the presence of the transgene in those plants. All the 73 plants also produced PCR products when tested with the specific primer 35S-496- F/OsDREB1A-R, indicating that transgene integration was maintained during the development of BC4F2 and BC5F1.